Pilot study examining anti-factor Xa levels for heparin monitoring and outcomes in patients with cerebral venous thrombosis - Pirahanchi, Yasaman; Salottolo, Kristin; Burrell, Christian; Tang, Xu; Bar-Or, David; Bartt, Russell (Frontiers in Medicine, 2024)
Objective There are no studies to date that examine the association between anti-factor-Xa (AFXa)-based heparin monitoring and clinical outcomes in the setting of cerebral venous thrombosis (CVT). Methods This pilot study included adults aged ≥18 admitted with CVT between 1 January 2018 and 1 January 2021, who were treated with unfractionated heparin (UFH) and were monitored via AFXa-based nomogram within 24 h of arrival. Comparisons were made between patients with AFXa levels within the target therapeutic range (0.25–0.5 IU/mL) and patients whose levels were not within the therapeutic range within 24 h of arrival; the time (hours) from arrival to reach the therapeutic range was also examined. Outcomes were length of stay (LOS) in the hospital, major (actionable) bleeding events, and discharge home (vs. higher acuity location). Continuous data are reported in the form of the median (interquartile range). Results Among 45 patients, treatment with UFH was initiated 2 (1–11) h after arrival, and the majority (84%) of UFH infusions did not need dose adjustment. AFXa assays were conducted every 6 (5.5–7) h. Thirty patients (67%) fell within the therapeutic range. Outcomes were similar for patients with levels within the therapeutic range vs. not: major bleeding events, 10% vs. 0% (p = 0.54); discharge home, 77% vs. 80% (p = 1.0); LOS, 5 days in each group (p = 0.95). There was also no association between outcomes and time to reach the therapeutic range. Conclusion Our findings demonstrate the practicability of monitoring UFH based on AFXa values in this population of patients with CVT, but reaching target AFXa levels within 24 h of arrival may not necessarily be prognostic.